Investigation on characteristics of blended cements containing pumice. (15th August 2016) - Ulusu, Hayati; Aruntas, Huseyin Yilmaz; Gencel, Osman
Highlights: We studied effect of pumice on properties of blended cement pastes and mortars. Pumice usage decreases mechanical properties of mortar while increasing durability. Specific gravity is decreased by the usage of pumice. Pumice decreases shrinkage strains of mortars. Abstract: In this experimental study, the effects of 10, 20, 25, 30 and 40 wt.% pumice addition on properties of blended cement pastes and mortars were investigated. Pumice blended cements with a high fineness were produced by intergrinding Portland cement clinker, pumice and gypsum. Characteristics such as particle size distribution, soundness, setting times, chemical analysis, compressive and bending strengths, drying shrinkage, autoclave expansion and sulfate resistance were determined. In addition, the microstructures of some samples scanned by scanning electron microscopy were photographed. Compressive strengths of mortars produced with pumice blended cements were lower than that of Portland cement tested ages up to 360 days. Pumice blended cements increase durability, sulfate expansion, shrinkage and autoclave expansion.